ESTIMATION OF PEDESTRIAN COMFORT ON THE BASIS OF NUMERICAL MODELING OF WIND AERODYNAMICS OF BUILDINGS IN THE ENVIRONMENTAL DEVELOPMENT - Alexander Belostotsky; Irina Afanasyeva; Irina Lantsova (International Journal for Computational Civil and Structural Engineering, 2019)
The distinctive paper is devoted to the methodology of pedestrian comfort estimation in the nearby area of the object under construction. A verification example of the wind flow simulation around and through a porous object is considered in order to select correct permeability parameters of the computational model of green spaces. The methodology of pedestrian comfort estimation is tested on the example of a real residential complex in Moscow. The results of the numerical simulation of velocity fields are used to calculate the criteria for pedestrian comfort specified in MDS 20-1.2006. Numerical results are obtained and compared for two study cases - without and with green spaces (bushes),to assess their impact on pedestrian comfort and the possibility of its adjustment.